The great man. - Rees, Marc Ryan (My University, 2011)
The topic of greatness in people is not one which has received much direct attention in philosophical literature. This paper aims to provide insight into the nature of greatness for humans by looking at how the concept of greatness is structured, how it relates to the concepts of (moral) goodness and of admiration, and by examining theories on what greatness is. Greatness is found to be aspectual in that something is great qua a certain aspect of it, and that greatness is a compound higher-order value. Greatness is discovered to be that which ought to be admired, where the “ought” is a special ought of propriety. Greatness is shown to be other than merely a superlative form of moral goodness, although extreme goodness can make for greatness. The means by which specific virtues produce greatness in people is also examined. Special rights and duties between great people and lesser ones are explored, based on matters of respect. Three theories of greatness are rejected: that greatness is (moral) goodness; greatness is perfection; greatness is reality (in a special Nozickian sense). Finally, I develop and tentatively accept a theory that greatness is an ennobling transcendence of a thing from its type.